2011
DOI: 10.1097/ta.0b013e31821858e6
|View full text |Cite
|
Sign up to set email alerts
|

Heart Rate Variability Is an Independent Predictor of Morbidity and Mortality in Hemodynamically Stable Trauma Patients

Abstract: Decreased VLF is an independent predictor of mortality and morbidity in hemodynamically stable trauma patients. Other time and other frequency domain variables correlated with some, but not all, outcomes. All were heavily influenced by factors that alter autonomic function, especially patient age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 32 publications
2
39
0
1
Order By: Relevance
“…Evidence of reduced HRV after TBI implies reduced parasympathetic tone (Baguley et al, 2006). With TBI, HRV has been shown to predict brain death and cerebrovascular dysregulation (Ryan et al, 2011), and HRV is associated with autonomic dysfunction in multiple other pathological states including sepsis, shock, and adrenal insufficiency (Morris et al, 2007; Werdan et al, 2009), each of which can co-occur in TBI. Further work suggests that HRV can be an effective mortality predictor, among hemodynamically stable patients with TBI (Ryan et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence of reduced HRV after TBI implies reduced parasympathetic tone (Baguley et al, 2006). With TBI, HRV has been shown to predict brain death and cerebrovascular dysregulation (Ryan et al, 2011), and HRV is associated with autonomic dysfunction in multiple other pathological states including sepsis, shock, and adrenal insufficiency (Morris et al, 2007; Werdan et al, 2009), each of which can co-occur in TBI. Further work suggests that HRV can be an effective mortality predictor, among hemodynamically stable patients with TBI (Ryan et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…With TBI, HRV has been shown to predict brain death and cerebrovascular dysregulation (Ryan et al, 2011), and HRV is associated with autonomic dysfunction in multiple other pathological states including sepsis, shock, and adrenal insufficiency (Morris et al, 2007; Werdan et al, 2009), each of which can co-occur in TBI. Further work suggests that HRV can be an effective mortality predictor, among hemodynamically stable patients with TBI (Ryan et al, 2011). Importantly, there is evidence that BDNF levels (Pal et al, 2014), BDNF genetic variability (Yang et al, 2010), and cortisol levels (Pal et al, 2014) are associated with HRV, making autonomic instability a plausible mechanism by which cortisol regulation of BDNF affects mortality risk.…”
Section: Discussionmentioning
confidence: 99%
“…3 HRV is increasingly gaining popularity as a predictor of outcome in a variety of clinical environments, including trauma patients, 12 critically ill emergency department 4 patients, 13 septic patients on admission to ED, 14 and the haemodynamically stable trauma patient. 15 It has also been used to predict outcomes such as hypotension during obstetric spinal hypotension. 16,17 Its use in ICU and anaesthesia has been extensively reviewed elsewhere.…”
Section: Discussionmentioning
confidence: 99%
“…6,8,14 For example, a recent report demonstrated that reduced HRV was an independent predictor of morbidity and mortality in 216 hemodynamically stable trauma patients with evidence of traumatic brain injury upon hospital arrival. 6 Importantly, however, the aforementioned study acknowledges that HRV analysis was completed a few hours to 3 days after initial measurement, which limits usefulness for clinical decision making. Similarly, Cancio et al 4 noted that analysis of HRV parameters required long processing times, which limits clinical utility.…”
Section: Discussionmentioning
confidence: 99%